(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
Kierkegaard’s notion of the ’Knight of Faith’ is examined in his short treatise Fear and Trembling. Although the thoughts are slanted towards the religious in the biblical story of Abraham and Isaac, Kierkegaard shows that his concepts offer an existential idea of living passionately against a life of uncertainty.